Rhein Protects Against Severe Acute Pancreatitis In vitro and In vivo by Regulating the JAK2/STAT3 Pathway - Yang, Xiaofang; Geng, Huan; You, Lijiao; Yuan, Lin; Meng, Jialei; Ma, Yuhui; Gu, Xuelian; Lei, Ming (Frontiers in Pharmacology, 2022)
Dachengqi Decoction is a classic traditional Chinese medicine prescription with strong anti-inflammatory effects. Rhein is the major active component of Dachengqi Decoction, but its effects on severe acute pancreatitis (SAP) have not been studied closely. This study investigated rhein’s protective effects against SAP using in vitro and in vivo models to determine whether its protective mechanism regulated the JAK2/STAT3 signalling pathway. AR42J cells were randomly divided into the control, cerulein and rhein groups. Amylase activity was assessed using an amylase test kit; the tumour necrosis factor-α (TNF-α) expression was determined by enzyme-linked immunosorbent assay (ELISA). JAK2 and STAT3 mRNA and protein expression were evaluated by reverse transcription-quantitative polymerase chain reaction and western blot. Thirty-six male Sprague–Dawley rats were randomised into sham operation, SAP and rhein groups. The SAP model was induced by retrograde pancreatic bile duct injection of sodium taurocholate. Serum TNF-α and interleukin (IL)-6 levels were determined by ELISA, whereas serum amylase and lipase concentrations were measured using test kits. The reverse transcriptase-qualitative polymerase chain reaction and western blot and/or immunohistochemistry quantified JAK2 and STAT3 expression. Furthermore, histopathological pancreatic changes were detected by haematoxylin and eosin staining. Rhein significantly reduced amylase activity in supernatants of AR42J cells induced by cerulein in vitro. Furthermore, rhein altered JAK2 and STAT3 mRNA and protein levels in AR42J cells after cerulein induction. SAP was concomitant with increased JAK2 and STAT3 expressions in vivo. Pre-treatment with rhein attenuated serum TNF–α and IL-6 levels effectively, significantly downregulated JAK2 and STAT3 mRNA expression and notably reduced p-JAK2, p-STAT3, JAK2 and STAT3 protein expression. Rhein significantly alleviated pancreatic histopathology, Overall, rhein exerted protective effect on SAP in vitro and in vivo, possibly through the JAK2/STAT3 signalling pathway.